Impact of Targeted Educational Interventions on Clostridium difficile Infection Treatment in Critically Ill Adults. Issue 11 (December 2016) - Hammond, Drayton A.; Hughes, Catherine A.; Painter, Jacob T.; Pennick, Rose E.; Chatterjee, Kshitij; Boye, Bradley; Meena, Nikhil
Background: Clostridium diffcile infection (CDI) is a growing clinical and economic burden throughout the world. Pharmacists often are members of the primary care team in the intensive care unit (ICU) setting; however, the impact of pharmacists educating other health care providers on appropriateness of CDI treatment has not been previously examined. Objective: This study was performed to determine the impact of structured educational interventions on CDI treatment on appropriateness of CDI treatment and clinical outcomes. Methods: This was a single-center, retrospective, cohort study of patients with CDI in the medical ICU at an academic medical center between January and June 2014 (pre-period) and 2015 (post-period). All patients were evaluated for appropriate CDI treatment before and after implementing pharmacist-provided educational interventions on CDI treatment. Results: Patients in the post-period were prescribed appropriate CDI treatment more frequently than patients in the pre-period (91.7% vs 41.7%; p = .03) and received fewer inappropriate doses of a CDI treatment agent (14 doses vs 30 doses). Patients in the pre-period had a shorter ICU length of stay [1.5 days (range, 1–19) vs 3.5 days (range, 2–36); p = .01] and a similar hospital length of stay [9.5 days (range, 4–24) vs 11.5 days (range, 3–56); p = .30]. Total time spent providing interventions was 4 hours. Conclusion: Patients had appropriate CDI treatment initiated more frequently in the post-period. This low-cost intervention strategy should be easy to implement in institutions where pharmacists interact with physicians during clinical rounds and should be evaluated in institutions where interactions between pharmacists and physicians occur more frequently in non-rounding situations.